Photo -induced Electron Transfer Between Ruthenium (II) tris –(2,2  - bipyrdine ) and Methyl Viologen - Al-Agealy, H.J.M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Electron transfer (ET) reactions represent an elementary chemical process which occurs in a large  variety of molecules, ranging from small ion pairs up to large biological system.      A theoretical study of photo â€“ induced electron transfer between Ruthenium (II) tirs -( 2,2 ï‚¢- bipyrdine ) Ru(bpy) ï€« 2 3 and Methyl Viologen MV2+ in a variety of Solvents at room temperature is presented . This study is based on an optical activation by the absorption of light .The Solvent is described by a dielectric continuum model, and  the transferring is represented by a quantum mechanical wave function . In this application, the reorganization energy ï¬ , the driving free energy ï¯ Gï„ , and the activation free energy G ï„ â€¡ are calculated with semi classical model . The electronic coupling for the electron transfer DA V reaction is taken from Mulliken â€“Hush method, and the rate of electron transfer KET in ï€« ï€« ï€ 2 2 3( ) Ru bpy MV system are calculated with a quantum mechanical model.      Our calculation results for the electron transfer in ï€« ï€« ï€ 2 2 3( ) Ru bpy MV system show a good agreement with the experimentally observed results .